Therapeutic concentrations of raloxifene augment nitric oxide-dependent coronary artery dilatation in vitro - Leung, F P (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Raloxifene improves cardiovascular function. This study examines the hypothesis that therapeutic concentrations of raloxifene augment endothelium-dependent relaxation via up-regulation of eNOS expression and activity in porcine coronary arteries. EXPERIMENTAL APPROACH: Isometric tension was measured in rings from isolated arteries. Intracellular Ca(2+) concentrations ([Ca(2+)](i)) in arterial endothelial cells were detected by Ca(2+) fluorescence imaging. Phosphorylation of eNOS at Ser-1177 was assayed by Western blot analysis. KEY RESULTS: In arterial rings pre-contracted with 9,11-dideoxy-11α,9α-epoxy-methano-prostaglandin F(2α) (U46619), treatment with raloxifene (1-3 nM) augmented bradykinin- or substance P-induced relaxation and this effect was antagonized by ICI 182,780, an estrogen receptor antagonist. The enhanced relaxation was abolished in rings treated with inhibitors of nitric oxide/cyclic GMP-dependent dilation, N(G)-nitro-L-arginine methyl ester (L-NAME) plus 1H-[1,2,4]oxadizolo[4,3-a]quinoxalin-1-one (ODQ). In contrast, effects of raloxifene were unaffected after inhibition of endothelium-derived hyperpolarizing factors by charybdotoxin plus apamin. Raloxifene (3 nM) did not influence endothelium-independent relaxation to sodium nitroprusside. 17ß-Estradiol (3-10 nM) also enhanced bradykinin-induced relaxation, which was inhibited by ICI 182,780. Treatment with raloxifene (3 nM) did not affect bradykinin-stimulated rise in endothelial cell [Ca(2+)](i). Raloxifene, 17ß-estradiol, and bradykinin increased eNOS phosphorylation at Ser-1177 and ICI 182,780 prevented effects of raloxifene or 17ß-estradiol but not that of bradykinin. Raloxifene had neither additive nor antagonistic effects on 17ß-estradiol-induced eNOS phosphorylation. CONCLUSIONS AND IMPLICATIONS: Raloxifene in therapeutically relevant concentrations augmented endothelial function in porcine coronary arteries in vitro through ICI 182,780-sensitive mechanisms that were associated with increased phosphorylation of eNOS but independent of changes in endothelial cell [Ca(2+)](i).